2016
DOI: 10.1016/j.heares.2016.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear perfusion with a viscous fluid

Abstract: The flow of viscous fluid in the cochlea induces shear forces, which could provide benefit in clinical practice, for example to guide cochlear implant insertion or produce static pressure to the cochlear partition or wall. From a research standpoint, studying the effects of a viscous fluid in the cochlea provides data for better understanding cochlear fluid mechanics. However, cochlear perfusion with a viscous fluid may damage the cochlea. In this work we studied the physiological and anatomical effects of per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…These simulations are analogous to a recent experiment by Wang and Olson ( 54 ). In the experiment, they perfused viscous fluids into the scala tympani through the open round window.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…These simulations are analogous to a recent experiment by Wang and Olson ( 54 ). In the experiment, they perfused viscous fluids into the scala tympani through the open round window.…”
Section: Resultssupporting
confidence: 83%
“…
Figure 4 Effect of fluid viscosity. Different levels of fluid viscosity were simulated, and results were compared with experimental data (Wang and Olson, ( 54 ), their Fig. 3, C and D ).
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One drug delivery technique in particular perfuses solutions throughout the cochlear length by injecting at relatively high rates (2 – 5 uL/min) into the basal turn of scala tympani with an outlet, or fenestration, for flow made at the apex or in the basal turn of scala vestibuli (e.g., Konishi & Kelsey 1968; Kujawa et al 1995; Bobbin & Salt 2005; Wang & Olson 2016). There are several problems that arise from patent fenestrations used with cochlear drug perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…These extraordinary properties of hearing depend on traveling waves of motion that propagate along both the basilar membrane and tectorial membrane (TM), ultimately stimulating mechanosensory receptors. Classical models of cochlear mechanics suggest that the spectral resolution of hearing is limited by viscous damping in the subtectorial fluid, and that cochlear amplification is required to compensate ( 1 , 2 , 3 , 4 , 5 , 6 ). However, several studies have shown that wave motions of the TM may play an important role in determining frequency tuning in a fundamentally different way—by longitudinally coupling many sensory receptor cells ( 7 , 8 , 9 , 10 , 11 , 12 ).…”
Section: Main Textmentioning
confidence: 99%